Industrial process sensors - Scott, David M. 1959- (CRC Press, 2008)
As manufacturing processes become more complex, industry must rely on advanced sensor technology and process control to improve efficiency and product quality. This text explores the physical theory, design, and implementation of sensors used to control manufacturing processes.
Keywords: Engineering instruments.; Detectors.; elektronické knihy; electronic books